A systematic review of adolescent physiological development and its relationship with health-related behaviour: a protocol. Issue 1 (December 2016) - Pringle, Jan; Mills, Kate; McAteer, John; Jepson, Ruth; Hogg, Emma; Anand, Neil; Blakemore, Sarah-Jayne
Abstract Background At any one time, there are one billion people worldwide who are in the second decade of their life, and 1.8 billion in the 10–24 age range. Whilst a great deal of focus has been placed on healthy early years development, the adolescent years are also a unique period of opportunity: exposure to health-influencing behaviours such as alcohol consumption or cigarette smoking, may serve to establish patterns that have significant health consequences in later life. Although there is often an emphasis on risk-taking and detrimental health behaviours during adolescence, these years also provide significant opportunities for behaviour to be shaped in positive ways that may improve longer term health outcomes. However, it is firstly important to understand the complex physiological changes that are taking place within the human body during this period and their relationship with health-related behaviour. Such knowledge can help to inform health policy and intervention development. Aim The aim of this study is to gain a comprehensive understanding of the relationship between physiological development and health-related behaviours in adolescence. Methods The principles of an integrative review will be used. Such reviews are of use where research has emerged in different fields, to combine existing knowledge and produce a more extensive understanding. Studies from a range of different methodological approaches, published or unpublished, will be included. A range of databases and literature depositories will be searched using a pre-defined search strategy. The review will include studies that focus on adolescents (nominally, those aged 10–24 years). We will seek papers that focus on both physiological development and health behaviour, or papers focusing solely on physiological development if there are clear implications for health behaviour. Studies with a focus on participants with specific health conditions will be excluded. Two reviewers will independently screen potential studies for eligibility and quality; members of the project team will act as third reviewers in the case of uncertainty or discrepancy. Further analyses (e.g. meta-analysis, meta-synthesis, meta-summary) will be decided upon, and sub-set analyses carried out. Finally, an integrative summation will be produced, giving a critical analysis of the results and providing conclusions and recommendations.